2004
DOI: 10.2337/diacare.27.8.1897
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Early Irbesartan Treatment Versus Control (Standard Antihypertensive Medications Excluding ACE Inhibitors, Other Angiotensin-2 Receptor Antagonists, and Dihydropyridine Calcium Channel Blockers) or Late Irbesartan Treatment in Patients With Type 2 Diabetes, Hypertension, and Renal Disease

Abstract: OBJECTIVE -The aim of this study was to determine the most cost-effective time point for initiation of irbesartan treatment in hypertensive patients with type 2 diabetes and renal disease. RESEARCH DESIGN AND METHODS-This study was a Markov model-simulated progression from microalbuminuria to overt nephropathy, doubling of serum creatinine, endstage renal disease, and death in hypertensive patients with type 2 diabetes. Two irbesartan strategies were created: early irbesartan 300 mg daily (initiated with micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
64
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 22 publications
(10 reference statements)
1
64
0
1
Order By: Relevance
“…Clinical practice guidelines advocate early detection and appropriate treatment based on the rationale that intervention in the early course of disease may be more advantageous. 1,2 To establish drug efficacy in clinical trials of progression of CKD doubling of serum creatinine and ESRD are used as clinical end points. However, progression of kidney disease to ESRD takes many years to manifest.…”
mentioning
confidence: 99%
“…Clinical practice guidelines advocate early detection and appropriate treatment based on the rationale that intervention in the early course of disease may be more advantageous. 1,2 To establish drug efficacy in clinical trials of progression of CKD doubling of serum creatinine and ESRD are used as clinical end points. However, progression of kidney disease to ESRD takes many years to manifest.…”
mentioning
confidence: 99%
“…12 Three treatment strategies were compared: early use of irbesartan (with therapy initiated when microalbuminuria was detected), late use of irbesartan (treatment started when nephropathy developed), and standard antihypertensive therapy with comparable BP control. 12 Data were taken from IRMA II and the IDNT; 12 costs for ESRD and outcomes were obtained from the USRDS. 12 Costs and This study demonstrated that, when compared with standard antihypertensive therapy, early use of irbesartan per 1,000 patients was projected to save $11.9 ± 3 million, and late use of irbesartan was projected to save $3.3 ± $2.7 million.…”
mentioning
confidence: 99%
“…12 Data were taken from IRMA II and the IDNT; 12 costs for ESRD and outcomes were obtained from the USRDS. 12 Costs and This study demonstrated that, when compared with standard antihypertensive therapy, early use of irbesartan per 1,000 patients was projected to save $11.9 ± 3 million, and late use of irbesartan was projected to save $3.3 ± $2.7 million. The study also estimated that the early use of irbesartan would add 1,550 ± 270 cumulative life years per 1,000 patients, while late use added only 71 ± 40 cumulative life years.…”
mentioning
confidence: 99%
See 2 more Smart Citations